How Resilient and Countercyclical Were Emerging Economies to the Global Financial Crisis? - Didier, Tatiana (Elsevier, 2013)
By studying the cross-country incidence of the 2008–2009 global financial crisis, we document a structural break in the way emerging economies responded to the global shock. Contrary to popular perceptions, emerging economies suffered growth collapses (relative to the pre-crisis levels) comparable to those experienced by developed economies, even when they continued growing. Afterwards, most economies returned to their pre-crisis growth rates. Although emerging economies were not able to avoid the collapse originated in the U.S. and then transmitted across countries, they were more resilient during the global crisis than during past crises. Namely, they resumed their higher growth rates earlier and converged more quickly to their pre-crisis growth trend. Moreover, breaking with the past, emerging economies did not fall more than developed economies during the global crisis and were able to conduct countercyclical policies, thus becoming more similar to developed economies.